The hard ECU — A substitute for the D-Mark or a trojan horse? - Rolf H. Hasse; Thomas Koch (Intereconomics, 1991)
The British Government≐s proposal to develop the ECU gradually into a “hard” European currency has begun to be viewed in a more positive light. What principles are at the heart of this proposal? Does a “hard” ECU have advantages over the existing ECU? What are its chances as a parallel currency?
Keywords: 330; European Community